Are fishers poor? Getting to the bottom of marine fisheries income statistics. Issue 3 (29th January 2020) - Teh, Lydia C. L.; Ota, Yoshitaka; Cisneros‐Montemayor, Andrés M.; Harrington, Lucy; Swartz, Wilf
Abstract: Fishers' economic status is hard to assess because fisheries socio‐economic data, including earnings, are often not centrally available, standardized or accessible in a form that allows scaled‐up or comparative analyses. The lack of fishing income data impedes sound management and allows biased perceptions about fishers' status to persist. We compile data from intergovernmental and regional data sets, as well as case‐studies, on income earned from marine wild‐capture fisheries. We explore the level and distribution of fishers' income across fisheries sectors and geographical regions, and highlight challenges in data collection and reporting. We find that fishers generally are not the poorest of the poor based on average fishing income from 89 countries, but income levels vary widely. Fishing income in the large‐scale sector is higher than the small‐scale sector by about 2.2 times, and in high‐income versus low‐income countries by almost 9 times. Boat owners and captains earned more than double that of crew and owner‐operators, while income from fisheries is greater than that from agricultural work in 63% of countries in this study. Nonetheless, incomes are below national poverty lines in 34% of the countries with data. More detailed fishing income statistics is needed for quantitative scientific research and for supporting socio‐economic policies. Key gaps to address include the lack of a centralized database for fisheries income statistics and the coarse resolution at which economic statistics are reported internationally. A first step to close the gap is to integrate socio‐economic monitoring and reporting in fisheries management.